A Case Report of Donnai-Barrow Syndrome. (April 2021) - Robinson, Melissa K.; Coe, Kristi; Bradshaw, Wanda T.
Abstract : Background: A genetic disorder should be considered when an infant presents with multiple congenital anomalies. Because of the acute presentation of an infant with multiple life-threatening defects, a genetic diagnosis of a rare disorder took weeks to delineate. Clinical Findings: This case describes a late preterm infant who presented at birth with congenital diaphragmatic hernia, tetralogy of Fallot, cleft lip, low-set ears, and hypertelorism. Primary Diagnosis: Donnai-Barrow syndrome was the final diagnosis confirmed by a defect observed on the LRP2 (2q31.1) gene using sequence analysis. This is a rare disorder that presents with a variety of phenotypic features in infants. Interventions: Initial neonatal resuscitation in the delivery room included intubation, positive pressure ventilation, and oxygen supplementation. Extracorporeal membrane oxygenation therapy was initiated from day of life 3 to 15. Initial surgery included correction of the congenital diaphragmatic hernia, and further surgical procedures included tracheostomy, gastrostomy tube, circumcision, ventricular septal defect repair, and cleft lip repair. Physical, occupational, and speech therapies were also initiated. Outcomes: The infant was transported to a pediatric rehabilitation facility at 6 months of life for further management of his chronic lung disease requiring tracheostomy with ventilator dependence. Practice Recommendations: Early recognition and diagnosis of genetic syndromes can improve family education and guide treatment interventions. An underlying syndrome should be suspected when an infant presents with multiple congenital defects. Infants with Donnai-Barrow syndrome should have thorough cardiac, neurologic, ophthalmologic, audiologic, and renal examinations due to the gene mutation effects on those systems.